QR CODE-BASED E-MONEY APPLICATION IN HOMESTAY AS THE EASY OF PAYMENT TRANSACTION - Anak Agung Gde Satia Utama; Izzato Millati; Ajeng Risna Liatika; Eka Sheilla Wati; Reynaldo Bimantoro; Arrafi Pratama Andriono (Journal of Management and Business, 2018)
E-Money is one of the payment methods expected to attract tourists to stay at the place and also facilitate the payment process. This study focused on businesses in the lodging industry of homestay. The homestay was chosen because most homestays are still conventionally managed and the payment is still using cash, making homestays less attractive for tourists to stay especially for tourists who are accustomed to using E-Money or other non-cash payments. This study aims to improve the competitiveness of homestays in facing competition in the lodging industry through the use of QR code-based E-Money to facilitate payment transactions. The data used in this study was qualitative data. Qualitative data is data in the form of numbers and can be collected by means of interviews, analysis of documents, FGDs, observation, picture taking or video recording. The results of this study showed that homestay owners can improve their services through more modern payment methods so that customer payments are easier and faster with E-Money. The research output can be used as a concept for homestay business actors or those who want to open a homestay business in developing an enterprise system so that they can apply payment methods using E-Money and be able to compete in the increasingly tight lodging industry every year.